Effectiveness of Massage Therapy and Gentle Yoga with Prenatal Depression - Indriyani Makmun (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Depression is a psychological health problem that is often seen throughout the world, It hinders the functioning, creativity, happiness, and satisfaction of individuals, reduces their quality of life, and causes disruption of activities in doing their work. Depression is prevalent during pregnancy and affects women 10% to 49%. Women who are depressed are more likely to give birth prematurely and neonatal conditions are more likely to have low birth weight or low birth weight or low birth weight of <2500 grams) The purpose of the study is to find out how effective massage therapy and gentle yoga are against prenatal depression in, Mataram City in 2023. This study was conducted by conducting massage therapy and gentle yoga prenatal gentle yoga where the movement can reduce the level of depression, especially among pregnant women at high-risk ages. The research method carried out using Quasi Experiment with pretest posttest nonequivalent one-group design is research whose conclusions are obtained by comparing data before and after the intervention. The results showed a significant difference before and after massage therapy and gentle yoga interventions against depression in pregnant women, with a p-value of 0.000<0.005. Conclusion: There was a difference in average scores before and after gentle yoga and massage therapy interventions for prenatal depression.